PCR Amplification and Transcription for Site-Specific Labeling of Large RNA Molecules by a Two-Unnatural-Base-Pair System - Kimoto, Michiko; Yamashige, Rie; Yokoyama, Shigeyuki; Hirao, Ichiro (Journal of Nucleic Acids, 2012)
For the site-specific labeling and modification of RNA by genetic alphabet expansion, we developed a PCR and transcription system using two hydrophobic unnatural base pairs: 7-(2-thienyl)-imidazo[4,5-b]pyridine (Ds) and 2-nitro-4-propynylpyrrole (Px) as a third pair for PCR amplification and Ds and pyrrole-2-carbaldehyde (Pa) for the incorporation of functional components as modified Pa bases into RNA by T7 transcription. To prepare Ds-containing DNA templates with long chains, the Ds-Px pair was utilized in a fusion PCR method, by which we demonstrated the synthesis of 282-bp DNA templates containing Ds at specific positions. Using these Ds-containing DNA templates and a biotin-linked Pa substrate (Biotin-PaTP) as a modified Pa base, 260-mer RNA transcripts containing Biotin-Pa at a specific position were generated by T7 RNA polymerase. This two-unnatural-base-pair system, combining the Ds-Px and Ds-Pa pairs with modified Pa substrates, provides a powerful tool for the site-specific labeling and modification of desired positions in large RNA molecules.